Cannabidiol Reduces Short- and Long-Term High Glutamate Release after Severe Traumatic Brain Injury and Improves Functional Recovery - Cindy Santiago-Castañeda; Saúl Huerta de la Cruz; Christopher Martínez-Aguirre; Sandra Adela Orozco-Suárez; Luisa Rocha (MDPI AG, 2022)
This study aimed to determine if orally administered cannabidiol (CBD) lessens the cortical over-release of glutamate induced by a severe traumatic brain injury (TBI) and facilitates functional recovery. The short-term experiment focused on identifying the optimal oral pretreatment of CBD. Male Wistar rats were pretreated with oral administration of CBD (50, 100, or 200 mg/kg) daily for 7 days. Then, extracellular glutamate concentration was estimated by cortical microdialysis before and immediately after a severe TBI. The long-term experiment focused on evaluating the effect of the optimal treatment of CBD (pre- vs. pre- and post-TBI) 30 days after trauma. Sensorimotor function, body weight, and mortality rate were evaluated. In the short term, TBI induced a high release of glutamate (738% ± 173%; p < 0.001 vs. basal). Oral pretreatment with CBD at all doses tested reduced glutamate concentration but with higher potency at when animals received 100 mg/kg (222 ± 33%, p < 0.01 vs. TBI), an effect associated with a lower mortality rate (22%, p < 0.001 vs. TBI). In the long-term experiment, the TBI group showed a high glutamate concentration (149% p < 0.01 vs. SHAM). In contrast, animals receiving the optimal treatment of CBD (pre- and pre/post-TBI) showed glutamate concentrations like the SHAM group (p > 0.05). This effect was associated with high sensorimotor function improvement. CBD pretreatment, but not pre-/post-treatment, induced a higher body weight gain (39% ± 2.7%, p < 0.01 vs. TBI) and lower mortality rate (22%, p < 0.01 vs. TBI). These results support that orally administered CBD reduces short- and long-term TBI-induced excitotoxicity and facilitated functional recovery. Indeed, pretreatment with CBD was sufficient to lessen the adverse sequelae of TBI.